(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the results of a study on the assessment of students’ knowledge and skills in mathematics, the development of assignments and assessment criteria - on the example of the chapter "Simple fractions" in grade 5.